Isolasi dan Identifikasi Cemaran Bakteri Salmonella sp. pada Daging Ayam dan Ikan Mentah - Hasna Ul Maritsa; Fitratul Aini; Ardiansyah Saputra; Desri Santi Nurhakim; Greace Meisinta Sihombing (BIO-SITE |Biologi dan Sains Terapan, 2017)
Food is a basic need that must be free from microorganisms contamination Salmonella sp. is a gram-negative bacteria that often contaminates food, especially meat, and causes Salmonellosis disease. This study aims to isolate and identify Salmonella sp. which allegedly contaminating the sample of chicken meat and raw fish. Samples from traditional market around Jambi University. The tests were conducted at the Laboratory of Biotechnology and Engineering, Faculty of Science and Technology, Jambi University. Isolation was performed by dilution method on SSA medium (Salmonella Shigella Agar), isolates were characterized by macroscopic-microscopic morphology, and biochemical test. The results showed that raw chicken meat was positively contaminated with Salmonella sp., while fish meat was not. Gram-negative bacillus isolate character is yields H2S black deposits and is capable of fermenting glucose, lactose and sucrose.